Social and economic effects of marine protected areas in South Africa, with recommendations for future assessments. Issue 3 (3rd July 2021) - Mann-Lang, JB; Branch, GM; Mann, BQ; Sink, KJ; Kirkman, SP; Adams, R
Abstract : Research on the socio-economic aspects of marine protected areas (MPAs) in South Africa is reviewed to guide evaluation and integration. After a brief international review, we used declaration notices and management plans to determine the extent to which social and economic objectives have been included in the purpose statements of MPAs. We then reviewed the current state of knowledge about the social and economic effects of South African MPAs. While many MPAs have purposes and objectives that include some social and economic objectives, these are limited in scope. Most of the MPAs that were declared before 2019 did not include objectives directly related to people or their needs. Social or economic research has been undertaken in fewer than half of the 23 coastal MPAs. Literature is largely limited to: (i) studies on negative impacts of MPAs on adjacent rural communities; (ii) selected aspects of tourism; and (iii) various aspects related to resource use. A wide range of other tangible and intangible effects, including those experienced by a broader set of stakeholders and over differing scales of time and space, have seldom been addressed. A case study on the Tsitsikamma MPA exemplifies challenges associated with understanding the full scope of social and economic aspects of MPAs. We conclude with recommendations to address the challenges of building a better understanding of the social and economic effects of MPAs, ensuring that these are addressed in establishing or revising objectives for each MPA, and assessing the extent to which the objectives meet both human and environmental needs.